2008
DOI: 10.1111/j.1365-294x.2008.03754.x
|View full text |Cite
|
Sign up to set email alerts
|

Diverse historical processes shape deep phylogeographical divergence in the pollinating seed parasite Greya politella

Abstract: Understanding the historical framework in which species interactions have diversified across landscapes may help to partition the effects of vicariance and geographically variable selection in shaping the geographical mosaic of coevolving species. We used phylogeographical analyses of the pollinating seed parasite Greya politella (Lepidoptera: Prodoxidae) to define the historical processes that may have structured interactions of this species with its host plants across major biogeographical breaks in western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
55
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 121 publications
(154 reference statements)
3
55
1
Order By: Relevance
“…These species are self-incompatible , and previous studies have shown that the moths are the dominant pollinator of these plants at the study sites (Rich et al 2008;Thompson and Cunningham 2002;. Two of the plant species were chosen because they emit very different floral scent bouquets: Lithophragma parviflorum from Turnbull Wildlife Refuge (47 24.0'N, 117 34.0'W) in eastern Washington, and L. cymbalaria from the UC Santa Barbara Sedgwick Reserve in California (34 42.871'N, 120 2.999'W) .…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…These species are self-incompatible , and previous studies have shown that the moths are the dominant pollinator of these plants at the study sites (Rich et al 2008;Thompson and Cunningham 2002;. Two of the plant species were chosen because they emit very different floral scent bouquets: Lithophragma parviflorum from Turnbull Wildlife Refuge (47 24.0'N, 117 34.0'W) in eastern Washington, and L. cymbalaria from the UC Santa Barbara Sedgwick Reserve in California (34 42.871'N, 120 2.999'W) .…”
Section: Methodsmentioning
confidence: 91%
“…At least five of the nine species in the Lithophragma genus are involved in a mutualistic relationship with the G. politella moth species complex (Rich et al 2008;Thompson 2010;. These four cryptic moth taxa are defined by genetically distinct mitochondrial haplotype clusters (Rich et al 2008), and also show evidence of morphological divergence, albeit with partly overlapping morphological distributions . The plants and insects appear in different combinations at different sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some communities, however, insects other than Greya moths, especially solitary bees or bombyliid flies, contribute importantly to the pollination of woodland stars (17)(18)(19)(20). Nevertheless, the interaction between woodland stars and Greya moths has persisted for millions of years as the plants and moths have diversified (18,21).…”
mentioning
confidence: 99%
“…Woodland star species are pollinated by moths in the Greya politella species complex, which includes up to four geographically separated, and molecularly divergent, cryptic species (21). The study sites included all four lineages, hereafter labeled G. politella PNW, OR, CA, and SN for Pacific Northwest, southern Oregon, California, and southern Sierra Nevada, respectively.…”
mentioning
confidence: 99%